Perceived Social Status and Oral Health Among Medicaid Insured Adults in Iowa - Jennifer M.C. Sukalski; Natoshia M. Askelson; Julie C. Reynolds; Peter C. Damiano; Wei Shi; Xian Jin Xie; Susan C. McKernan (Health Equity)
Purpose: Perceived social status (PSS), a measure of social status, reflects cumulative lifetime effects of an individual’s relative social status based on resources and lived experiences. PSS is hypothesized to better capture social status compared to traditional measures of socioeconomic status (SES) (i.e., education, occupation, and income). Although recognized as a predictor of health-related morbidity and mortality, limited research has explored PSS and oral health. This study investigated PSS as a predictor of self-reported oral health among low-income adults. Methods: In spring 2018, a survey was administered to a random sample of low-income adults in the state of Iowa with public dental insurance (N = 18,000). Respondents were asked about PSS, oral health status, and demographics. Multivariable linear regression models examined PSS as a predictor of self-reported oral health and compared the predictive power of PSS and SES indicators. Results: The final adjusted sample size was 2,331. The mean PSS (range 1-10) was 5.3 (standard deviation 2.0). A significant positive association was noted between PSS (ß = 0.16, p < 0.0001) and self-reported oral health status when controlling for demographics. Furthermore, PSS accounted for an additional 3% of variance when controlling for demographic and SES indicators. Conclusions: PSS was associated with self-reported oral health status after adjusting for SES indicators, which reflects the importance of exploring the impact of individuals’ perceptions of their social status in addition to objective measures of SES. Results suggest the need for future dental research to explore cumulative effects of lived experiences on current oral health status.